1998
DOI: 10.1039/a707626f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a mordenite/ZSM-5/chabazite hydrophilic membrane on a tubular support. Application to the separation of a water–propanol mixture

Abstract: A selectivity of 71 is achieved in the separation of a gas phase water–propanol mixture, using a mordenite/ZSM-5/chabazite membrane that is hydrothermally synthesized onto the inner surface of a porous α-alumina tubular support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…16,17 However, these membranes are not suitable for separating small molecules because of their wide pore size distribution and the larger pore sizes of mordenite and MFI crystals, which constituted approximately 75% of the membrane. 16 Lee and Dutta 18 prepared pure, freestanding chabazite films. These films had weak mechanical stability and therefore were not used for separation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 However, these membranes are not suitable for separating small molecules because of their wide pore size distribution and the larger pore sizes of mordenite and MFI crystals, which constituted approximately 75% of the membrane. 16 Lee and Dutta 18 prepared pure, freestanding chabazite films. These films had weak mechanical stability and therefore were not used for separation.…”
Section: Introductionmentioning
confidence: 99%
“…Several membranes with the chabazite structure have been reported. Membranes consisting of a mixture of chabazite, mordenite, and ZSM-5 were synthesized on α-alumina supports and found to separate propanol/water vapor mixtures with a separation factor of 71. , However, these membranes are not suitable for separating small molecules because of their wide pore size distribution and the larger pore sizes of mordenite and MFI crystals, which constituted approximately 75% of the membrane . Lee and Dutta prepared pure, free-standing chabazite films.…”
Section: Introductionmentioning
confidence: 99%
“…The preferential size-selective reactivity of ammonia (2.6 # A) over tributyl amine (8.1 # A) on acidic chabazite/silica ®lms was reported by Bein and Brown [21]. Recently, Salomon et al reported the synthesis of mordenite/ZSM±5/ chabazite composite membrane on tubular a-alumina support [8]. Because of the high hydrophilicity, this composite membrane was used for the separation of water from ternary mixtures and showed a water/propanol selectivity as high as 149.…”
Section: Introductionmentioning
confidence: 99%
“…Substrates are typically immersed in the reaction mixture, and in some cases, the reaction container itself can act as a substrate. Various zeolites have been grown on the surfaces of organic polymers [4±7], porous alumina [8,9], glasses [10±12], and metals [5,13] using direct ®lm synthesis on substrates. The use of seeded substrates formed by depositing preformed crystals on substrates or laser ablation followed by further hydrothermal growth also allows for continuous ®lm formation [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The Beta crystals present in the top layer in sample B could have been formed from the slight aluminum substrate leaching (through ZSM-5 bottom layer) which acts as nutriment source. To some extent, Salomon et al [35] observed the same phenomenon while studying the synthesis of a mordenite/ZSM-5/chabazite membrane: if the MOR phase is expected according to the precursor gel composition, the leaching of alumina substrate in the synthesis media leads to the formation of MFI and CHA-type zeolite as impurities.…”
Section: Influence Of the Starting Gel Compositionmentioning
confidence: 80%